Measurement and behavior of the overall volumetric oxygen transfer coefficient in aerated agitated alkane based multiphase systems - Manyuchi, Musaida Mercy (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Process Engineering))--University of Stellenbosch, 2010.